Xilem study in roots of Arachis hypogaea subsp. hypogaea var hypogaea ev. Florman INTA (leguminosae) in soils with densified horizons (Semiárida, 2020)
The objective of-this work ís to study xylem characteristics of roots of Arachis hypogaea L. subsp. hypogaea var. hypogaea cv. "Florman INTA" in a typical Haplustoll soil with densified horizons and different hydrical condition. This study was carried out in two plots located in the subhumid dry region of Río Cuarto Department. Plot 1 shows higher mean humidity and lower mechanical impedance. Under these conditions, the diameter, wall thickness and frequency of vessel members are larger. Even though plants from both plots show similar total root and xilematic areas, roots from Plot 2 show lower values in vessel member characleristics. Therefore, they must have a higher proportion of parenchymatic tissue. This study demonstrates how small changes in soil water content affect xylem structure.
Keywords: Arachis; roots; xylem; anatomy; compacted horizons